Functional Analysis - Rudin, Walter (New Delhi: TMH, 1991)
This classic text is written for graduate courses in functional analysis. This text is used in modern investigations in analysis and applied mathematics. This new edition includes up-to-date presentations of topics as well as more examples and exercises. New topics include Kakutani's fixed point theorem, Lamonosov's invariant subspace theorem, and an ergodic theorem.
Appendix A-B 391-411p.; Bibliography 412-413p.; List of special symbols 414-416p.; Index 417-424p.
Keywords: Baire category; Bounded operators; Holomorphic functions; Sobolev lemma; Metrization